2019
DOI: 10.15252/embr.201847563
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic regulation of ferroptosis by H2B monoubiquitination and p53

Abstract: Monoubiquitination of histone H2B on lysine 120 (H2Bub1) is an epigenetic mark generally associated with transcriptional activation, yet the global functions of H2Bub1 remain poorly understood. Ferroptosis is a form of non‐apoptotic cell death characterized by the iron‐dependent overproduction of lipid hydroperoxides, which can be inhibited by the antioxidant activity of the solute carrier family member 11 (SLC7A11/xCT), a component of the cystine/glutamate antiporter. Whether nuclear events participate in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
94
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 144 publications
(108 citation statements)
references
References 66 publications
3
94
0
Order By: Relevance
“…SLC7A11 and GPX4 are considered as the central regulators of ferroptosis, and reduced levels of GPX4 and SLC7A11 are always regarded as markers of ferroptosis [56][57][58]. In our study, we found that both SLC7A11 and GPX4 were clearly decreased in the LPS-induced ALI model, suggesting that ferroptosis occurred during the process of LPS-induced ALI.…”
Section: Discussionsupporting
confidence: 58%
“…SLC7A11 and GPX4 are considered as the central regulators of ferroptosis, and reduced levels of GPX4 and SLC7A11 are always regarded as markers of ferroptosis [56][57][58]. In our study, we found that both SLC7A11 and GPX4 were clearly decreased in the LPS-induced ALI model, suggesting that ferroptosis occurred during the process of LPS-induced ALI.…”
Section: Discussionsupporting
confidence: 58%
“…Cytokine signaling 1 (SOCS1) is required for p53 activation and the regulation of cellular senescence, and SOCS1 is sufficient to regulate the expression of p53 target genes and sensitized cells to ferroptosis by reducing the expression of the cystine transporter SLC7A11 and the levels of GSH (Saint-Germain et al, 2017). Histone H2B on lysine 120 (H2Bub1) is an epigenetic mark generally associated with transcriptional activation, and H2Bub1 epigenetically activates the expression of SLC7A11, but p53 decreases H2Bub1 occupancy on the SLC7A11 gene regulatory region and represses the expression of SLC7A11 during ferroptosis process (Wang et al, 2019f). Recently, the OTU domain, ubiquitin aldehyde binding 1 (OTUB1) was demonstrated as a key factor in modulating SLC7A11 stability.…”
Section: The Glutathione Peroxidase 4 Synthesis and Function-relatedmentioning
confidence: 99%
“…80 Another study reported that p53 repressed the expression of SLC7A11 during erastin treatment by decreasing H2Bub1 occupancy on the SLC7A11 gene regulatory region. 81 indicating that p53 has a pro-survival function. 82 Wild-type p53 has been reported to delay the onset of ferroptosis in response to cystine deprivation via the p53-p21 axis to mitigate the depletion of intracellular glutathione and reduce accumulation of lethal lipid ROS.…”
Section: Role Of P53 In Ferrop Tos Ismentioning
confidence: 99%